India's Contribution during COVID-19 Pandemic: COVISHIELD and COVAXIN - Kusum K Rohilla; Deepak Rohilla; Bhagwati Devi; Parvin K Yadav; Kamlesh Malik; Mahendra K Saini (Medsci Publications, 2021)
Coronavirus disease-2019 pandemic is presently wreaking havoc on general public health, food systems, human dignity, and labour around the world. The availability and potential delivery of a safe and effective vaccination to communities around the world is being viewed not only as a means of overcoming these obstacles, but also as a demonstration of human resilience in the face of hardship. Nations must mobilise their resources to ensure widespread access to vaccines, without which the true benefits of development will be lost. Despite its vast internal needs, our country is seen with both hope and anticipation for its ability to deliver at this critical moment in human civilization's progress, and India is more than willing to contribute.